Implementasi Aspek Kognitif dalam Kegiatan Muhadhoroh di SMP N 1 Jetis Ponorogo - Wahyu Risky Pratama; Siti Mu'alifah; Suci Aisyah Ningtias; Syahriatur Rohmah; Vina Tri Nur Astuti; Wahid Nur Rohman; Nurul Malikah (https://ejournal.insuriponorogo.ac.id/, 2024)
The aim of this research is to examine how SMPN 1 JetisPonorogo implements cognitive elements in muhadhoroh activities. As a public speaking teaching method, muhadhoroh has the ability to improve students' cognitive abilities, including information synthesis, analysis and critical thinking. This research uses case study methodology and qualitative techniques which include document analysis, interviews and observations. Research findings show that by offering difficult material and encouraging group debate, muhadhoroh training at SMPN 1 Jetis includes cognitive elements in addition to technical speaking skills. Students' critical and analytical thinking skills are improved by being encouraged to carry out research on the subjects that will be presented. Additionally, input from peers and instructors plays an important role in helping children improve their cognitive abilities.